Adjustment of the Optical Properties of Dispersion Derived Carbon Nanotube Coatings1 . Issue 4 (8th October 2015) - Weisenseel, Bastian; Zierath, Bodo; Fey, Tobias; Greil, Peter
Abstract : Porous carbon nanotube coatings for potential solar thermal receiver applications were generated on silicon carbide via an infiltration process from an aqueous dispersion. A screening evaluation was applied to generate carbon nanotube coatings with enhanced absorption, i.e., reduced reflection of solar wavelength spectra from 2 500–500 nm. Structures with low density nanotube packing with a total reflectance <2% were fabricated from a low concentration dispersion of sterically stabilized (PVP) carbon nanotubes. Though the optical performance is lower when compared to carbon nanotube coatings generated by CVD, the filtration method offers control of the nanotube pore structure over a wide range, a greater flexibility with regards to substrate geometry and excellent up‐scaling capability. Abstract : In this work, a solution approach is described to produce carbon nanotube coatings on silicon carbide, while controlling their optical properties by the different coating parameters. Furthermore, the usability of these coatings for solar thermal absorber applications is investigated, with regard to their optical and thermal properties.